Formulation and Characterization of Cetylpyridinium Chloride Bioadhesive Tablets - Jafar Akbari (Advanced Pharmaceutical Bulletin, 2014)
Purpose: Bioadhesive polymers play an important role in biomedical and drug delivery applications. The aim of this study is to develop a sustained- release tablet for local application of Cetylpyridinium Chloride (CPC). This delivery system would supply the drug at an effective level for a long period of time, and thereby overcome the problem of the short retention time of CPC and could be used for buccal delivery as a topical anti-infective agent. Methods: CPC bioadhesive tablets were directly prepared using 7 mm flat-faced punches on a hydraulic press. The materials for each tablet were weighted, introduced into the die and compacted at constant compression pressure. The dissolution tests were performed to the rotation paddle method and the bioadhesive strength of the tablets were measured. Results: The results showed that as the concentration of polymer increased, the drug release rate was decreased. Also the type and ratio of polymers altered the release kinetic of Cetylpyridinium Chloride from investigated tablets. The bioadhesion strength increased with increasing the concentration of polymer and maximum bioadhesion strength was observed with HPMC K100M. Conclusion: The selected formulation of CPC bioadhesive tablet can be used as a suitable preparation for continuous release of CPC with appropriate bioadhesion strength.